2001
DOI: 10.1111/j.1471-0528.2001.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism in pregnancy and the puerperium: incidence and additional risk factors from a London perinatal database

Abstract: Objective To determine the incidence of venous thromboembolism in pregnancy and the puerperium and to identify risk factors for pregnancy-related venous thromboembolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(88 citation statements)
references
References 17 publications
6
78
0
1
Order By: Relevance
“…While pregnancies have a higher risk of venous thrombosis than non-pregnant women of matched age [2]. The incidence appears to be increased in the postpartum period [3]. The possible increased risk of recurrent pregnancy loss or deep vein thrombosis can be classified as acquired or genetic risk factors, when genetic defects are combined with one or more acquired risk factors it results in a risk of DVT that exceeds the separate effects of a single factor [4].…”
Section: Introductionmentioning
confidence: 99%
“…While pregnancies have a higher risk of venous thrombosis than non-pregnant women of matched age [2]. The incidence appears to be increased in the postpartum period [3]. The possible increased risk of recurrent pregnancy loss or deep vein thrombosis can be classified as acquired or genetic risk factors, when genetic defects are combined with one or more acquired risk factors it results in a risk of DVT that exceeds the separate effects of a single factor [4].…”
Section: Introductionmentioning
confidence: 99%
“…The risk might have been significantly underestimated in our study as we only identified clinically significant DVT and did not investigate the prevalence of DVT in the puerperium period, which is reported to be several times higher than that of the antenatal period (Andersen et al, 1998;Simpson et al, 2001). …”
Section: Masamitsu Yanadamentioning
confidence: 81%
“…Our results were in agreement with previous reports as there were approximately twice and fi ve times as many postpartum as antepartum DVT events. 4,5 In contrast, James and colleagues reported more pregnant women suffer DVT in early pregnancy than in the puerperium. 6 In a meta-analysis, it was reported that about 82% of DVT occurred in the left lower extremity.…”
Section: Discussionmentioning
confidence: 94%
“…9 Yet blood group A, multiple pregnancy, caesarean section, cardiac disease, preterm delivery, high body mass index and elder women (Ͼ35 years) were found to increase incidence of VTE. 4 The association of blood group with DVT could explore the genetic predisposition (Factor V Leiden) of these groups to DVT. Although, we failed to observe an association between blood group and DVT, but those women who had family history of DVT were at higher risk of DVT.…”
Section: Discussionmentioning
confidence: 99%